Epidemiological Analysis and Management of Oral and Craniomaxillofacial Trauma in Indonesia: A Systematic Review - Fiki Muhammad Ridho; Alfi Syahri; Pulung Dwisari (Majalah Kedokteran Andalas, 2024)
Objective: This systematic review aims to analyze and review the epidemiological characteristics and management of oral and craniomaxillofacial trauma in patients in Indonesia. Methods: Using PRISMA guidelines, a systematic review of articles published in Scopus, PubMed, ScienceDirect, Google Scholar, and Garuda up to March 2024 was conducted. In selecting studies, inclusion and exclusion criteria were applied. Results: This study included 2,928 cases of oral and craniomaxillofacial trauma obtained from a total of 44 studies consisting of 25 case reports, 11 retrospective studies, 7 cross-sectional studies, and 1 case series. Summary results from pooled data, this study highlights that male patients predominate in all cases with a total of 80.70% and the male/female ratio is 4.2:1. Oral and craniomaxillofacial trauma occurred mostly in the 21-30 year age group (25.51%), followed by 11-20 year olds (24.15%) and 31-40 year olds (16.73%). Based on etiology, most cases occurred due to traffic accidents (87.88%). In the management of trauma cases, open reduction and internal fixation (ORIF) is the most frequently performed with a total of 66.71% of all cases. Conclusion: Oral and craniomaxillofacial trauma in Indonesia is dominated by male patients and in the productive age group with mandibular fractures being the highest cases.